MSGUI : um instrumento para avaliação de usabilidade em jogos sérios para dispositivos móveis - Schmidt, Jaison Dairon Ebertz (2017)
The launch of the iPhone with its resources based on touch screen, provided the start of a period of unprecedented technology mobility. The use of smartphones and tablets is already incorporated to the social custom and present in the most varied situations of daily life. The spread of mobile devices leveraged various possibilities of application, including serious games, whose objective is to provide improvements in some (or many) aspects of its users, like cognitive impairments, learning, health or just for entertainment purposes. Due to the diversity of the usage, Due to the diversity of uses and especially the public to which these games are intended, usability becomes an aspect of great importance, since serious game users may present physical and / or cognitive difficulties, therefore, facilitating the use and learning of these applications is essential. This paper aims to describe the process of elaboration of an instrument to evaluate the usability of serious games (MSGUI), their validation and results. The steps in the development of this instrument consisted in conduct a systematic literature review (SLR) in order to detect possible existing methods, protocols or instruments. As a result of this first SLR it was not possible to find the existence of pre-existing methods, protocols or instruments, although some evaluation procedures performed by researchers were similar. For the MSGUI elaboration, a new SLR was conducted with aims of to research guidelines and recommendations with focus in make better usability in serious games. As a result are listed guidelines about playability, design and several recommendations extracted from scientific works, serving as a compendium of desirable features in serious games. From this information the, was elaborated an electronic usability evaluation questionnaire, makes it possible to customize new questionnaires and the generation of reports containing sample characterization, usability, playability and design scores. This questionnaire was validated by an experiment with 30 users aged 55-64 years. This experiment compared the usability of two versions of the same game being the second version considered with a better usability (H0). Each user realized two test sessions, in the end of each session users responded the usability instrument. The results suggest that the instrument indicated a better usability in the second version, confirming the hypothesis suggested by the researchers.